Remote follow-up with a mobile application is equal to traditional outpatient follow-up after bariatric surgery: the BELLA pilot trial - Yang, Cui; Kessler, Mia; Taebi, Niki; Hetjens, Michael; Reißfelder, Christoph; Otto, Mirko; Vassilev, Georgi (Obesity surgery, 2023)
Medical follow-up after bariatric surgery is recommended. However, the compliance was poor. This study aimed to evaluate the feasibility of a smartphone-based fully remote follow-up (FU) program for patients after bariatric surgery.
Online veröffentlicht: 21. April 2023
Gesehen am 15.08.2024